BALANITES AEGYPTIACA PROTECTION AGAINST PROLIFERATION OF DIFFERENT CANCER CELL LINE - Al-Malki, Abdulrahman L.; Barbour, Elie K.; Abulnaja, Kalid O.; Moselhy, Said S.; Kumosani, Taha A.; Choudhry, Hani (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of the present study was to evaluate in vivo anti-tumor activity of Balanites aegyptiaca fruits extracts in additionto its role in cell cycle and apoptosis.Materials and Methods: Antitumor activities of ethylacetae extract (EAE), ethanol extract (EE) and chloroform extract (CE) were testedagainst different cell line Hep-2, MCF-7, HL-60 and HCV29T. Calculation of the IC50 values for these extracts confirmed that the mostpotent plant extract was EAE (40 ug/ml) followed by EE (55ug/ml), CE (61ug/ml).Results: The ethanolic and chloroform extracts showed lower difference in their potency, while the EAE was found to be more activeindicating for nonpolar active principles responsible for the anti-proliferative activity. The ethanolic extract was three times higher activethan the chloroform extract. The results obtained showed that EAE exert a significant anti-proliferative, enhancement of apoptosis andmodulation of cell cycle phases compared with vincristine.Conclusion: The presence of alkaloids, flavonoids and Phenolics increase its efficiency as anti-proliferative action. EAE has promisinganti-cancer activity with higher activity than EE or CE extracts